Synergistic Effects of Artesunate in Combination with Amphotericin B and Miltefosine against Leishmania infantum: Potential for Dose Reduction and Enhanced Therapeutic Strategies - Nuchpicha Intakhan; Atiporn Saeung; Sonia M. Rodrigues Oliveira; Maria de Lourdes Pereira; Wetpisit Chanmol (MDPI AG, 2024)
Leishmaniasis is a tropical infectious disease caused by Leishmania parasites. The disease can be spread by the bite of an infected sand fly. Currently, five chemotherapeutic drugs are available in leishmaniasis treatment. However, these drugs exhibit toxicity and serious adverse effects on infected individuals, necessitating alternative treatment strategies. One such strategy involves using combinations of existing antileishmanial drugs. In this study, we evaluated the interaction between artesunate (AS) and three antileishmanial drugs-amphotericin B (AmB), miltefosine (MF), and paromomycin (PM) against Leishmania infantum. This evaluation marks the first time such an assessment has been conducted. The Chou-Talalay combination index method was employed to analyze the drug interaction. The findings revealed that the interaction between AS and AmB ranged from antagonistic to synergistic, while the interaction between AS and MF showed moderate to strong synergism. In contrast, the interaction between AS and PM resulted in an antagonistic interaction, which differs from the combinations with AmB or MF. This study provides valuable insights for developing novel drug regimens for leishmaniasis treatment, emphasizing the potential of AS and its combination with existing antileishmanial drugs. Further research is necessary to optimize drug combinations and minimize adverse effects, leading to more effective therapeutic outcomes.